KONSEP BRAIN, BEAUTY AND BEHAVIOR (3B) PADA PROFESI PUBLIC RELATIONS - Intan Mustafa (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2019)
Qualification of Public Relations becomes a basic requirement for a company or organization. One of them is through the work of the front office in the banking industry. This study intends to examine the concept of 3B (Brain, beauty and behavior) into a work system based on Public Relations qualifications. with data collection techniques through interviews and observations to customers and front office employees at several banks in Sikka Regency. The results of data analysis carried out related to the implementation of the 3B concept are categorized based on the public relations qualifications namely: 1). Brain (A. ability to communicate ability in communication management based on 2 things, namely, knowledge and skill, b) Ability to Organize: Front officers are able to act as problem solvers in finding strategic solutions to problems related to products and services from banks. 2) Beauty (a. personal integrity, which includes 2 things namely a modest personality, and friendly and dress ethics, which contain aesthetic and ethical values 3) Behavior (a. Ability to get on with people, relationships based on customer satisfaction and providing good service. b. Imagination, insight and understanding of customer characteristics and mastering concepts, implementation in solving each problem responsibly and quickly). From the results of the research conducted, it was found that the front office performance in the banking industry has so far reflected the standard of a public relations officer.